Polypoid Adenomyoma of Endocervical Type - Yuka Takeda; Daiju Araki; Toru Arase; Yutaka Tsutsumi (Hindawi Limited, 2014)
We report herein a 53-year-old Japanese female case of polypoid adenomyoma of endocervical type. A sessile 16 mm sized cervical polyp, hard in consistency, was surgically removed. Histologically, the polypoid lesion was composed of smooth muscle bundles and scattered benign-looking endocervical glands. The mucin was diffusely alcianophilic. Immunohistochemically, some mucous glands were positive for MUC1 (CA15-3) and MUC5AC, and the other small glands were immunoreactive for MUC6. MUC2 and mucin characteristic of gastric gland mucous cells (M-GGMC-1 or HIK1083) were negative. Carcinoembryonic antigen was consistently expressed along the apical surface. Estrogen receptor was positive, while progesterone receptor was negative. Ki-67 labeling index was low. These findings were consistent with the endocervical nature of the mucin-producing columnar cells. This is the 18th case of adenomyoma of endocervical type reported in the English literature.